(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
When a newborn’s brain as well as organs are not supplied with enough oxygen immediately or shortly after birth, it can cause birth asphyxia, which can result in developmental problems or brain damage. In the Anbar province of Iraq, the neonatology departments of the Fallouja Teaching Hospital as well as the Almalaky Private Hospital participated in this case-control research. All moms gave their written informed permission. The information was gathered between November 2024 and March 2025. This research comprised women of newborn pairs delivered to the labor room. Revealed that while 20 to 25 years old was the most prevalent age group for both situations, there was no discernible difference (P = 0.553). Although it was not statistically significant (P = 0.269), the weight distribution revealed that a larger number of people in the control group (50%) weighed between 71 and 80 kg than in the case group (33.3%). The majority of patients in both groups were pregnant for one to three pregnancies, whereas the variations were also not statistically significant (P = 0.602). The case group had a greater percentage of people with elementary school education (52.8%), as well as fewer had college or institute education (22.2%) than the control group (43.8%), according to the educational level trend, albeit the P-value (0.071) did not support significance. In the research environment, birth asphyxia remains common. Birth asphyxia was caused by cyanosis, ammonitic fluid aspiration, infant birth weight, delivery type, and pregnancy length. The study’s findings highlight the need for improved mother care, educating maternity health workers on the variables that contribute to birth asphyxia, closely monitoring labor, and recognizing and implementing appropriate interventions to assist reduce the incidence of birth asphyxia.